2021
DOI: 10.1039/d0cc08048a
|View full text |Cite
|
Sign up to set email alerts
|

Non-symmetric mechanophores prepared from radical-type symmetric mechanophores: bespoke mechanofunctional polymers

Abstract: An non-symmetric radical-type mechanophore (CF/ABF) was synthesized by the molecular crossing between two radical-type mechanophores. Thermal stability and mechanoresponsiveness of CF/ABF were found to be tunable by the properties of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…[48][49][50] BMG,d espite its long history in the field, [51][52][53] has only recently saw ar esurgence in its popularity as as olid-state method. [36,37,43,[54][55][56] With US,simple linear polymers undergo chain-centered scission, with scission rates that are dependent on molecular weight;specifically,rates increase with increasing molecular weight. [50] Below al imiting molecular weight (M lim )the generated elongational forces are not great enough to cause chain scission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50] BMG,d espite its long history in the field, [51][52][53] has only recently saw ar esurgence in its popularity as as olid-state method. [36,37,43,[54][55][56] With US,simple linear polymers undergo chain-centered scission, with scission rates that are dependent on molecular weight;specifically,rates increase with increasing molecular weight. [50] Below al imiting molecular weight (M lim )the generated elongational forces are not great enough to cause chain scission.…”
Section: Introductionmentioning
confidence: 99%
“…US has emerged as the most popular solution‐state method for conducting polymer mechanochemistry [48–50] . BMG, despite its long history in the field, [51–53] has only recently saw a resurgence in its popularity as a solid‐state method [36, 37, 43, 54–56] . With US, simple linear polymers undergo chain‐centered scission, with scission rates that are dependent on molecular weight; specifically, rates increase with increasing molecular weight [50] .…”
Section: Introductionmentioning
confidence: 99%
“…Focus is placed on the printability and postprinting of latent MPs and fluorogenic print components. Chen et al [ 81 ], Calvino et al [ 82 ], Zhang et al [ 83 ] and Yanada et al [ 84 ] showed that choosing the correct MP–polymer combination for a specific application is very important when taking into account the MP activation method and the physico-mechanical properties of the polymer in accordance with the requirements for it.…”
Section: Current Topical Trends In Mechanochemistry Of Polymersmentioning
confidence: 99%
“…The weak bonds are defined as chemical bonds with a bond-dissociation energy (BDE) of less than 72 kcal mol -1 ; they are generally found in acyclic structures. These include covalent bonds such as diazo, 23,47 C-S, [48][49][50] C-C (in tetraarylsuccinonitrile), 25,28,[51][52][53][54][55][56] C-O, 50,57,58 S-S, [59][60][61][62] (Figure 2a), and coordinative bonds such as Ru-carbene, Ag-carbene, or Cucarbene bonds, 16,63 Fe-Cp (in ferrocene), [64][65][66] Pt-acetylide, 67 Fe-pyridine, 68 Cu-naphthalene, 69 Pd-phosphine, 70 and Pdcarbene (Figure 2b). 71 Covalent bonds in strained ring structures have lower BDEs than the analogous linear structures and can respond to mechanical forces.…”
Section: Cluster Account Synlettmentioning
confidence: 99%